Quality and stability of extemporaneous pyridoxal phosphate preparations used in the treatment of paediatric epilepsy. (21st February 2017) - Mohamed-Ahmed, Abeer H A; Wilson, Matthew P; Albuera, Maedelyn; Chen, Ting; Mills, Philippa B; Footitt, Emma J; Clayton, Peter T; Tuleu, Catherine
Abstract: Objectives: To assess the pyridoxal 5′-phosphate (PLP) content and stability of extemporaneous PLP liquids prepared from dietary supplements used for the treatment of vitamin B6 -dependent epilepsy. Methods: Pyridoxal 5′-phosphate liquids were prepared in accordance with the guidelines given to patients from marketed 50 mg PLP dietary capsules and tablets. The PLP content and its stability were evaluated under conditions resembling the clinical setting using reverse phase HPLC and mass spectrometry. Key findings: Pyridoxal 5′-phosphate content in most of the extemporaneously prepared liquids from dietary supplements was found to be different from the expected amount ( 16–60 mg). Most of these PLP extemporaneous liquids were stable at room temperature (protected from light) after 24 h but unstable after 4 h when exposed to light. A key photodegradation product of PLP in water was confirmed as 4-pyridoxic acid 5′-phosphate (PAP). Conclusion: Pyridoxal 5′-phosphate tablets from Solgar® were found to be the most reliable product for the preparation of extemporaneous PLP liquids. This work highlighted the difference between the marketed PLP dietary supplements quality and the importance of proper storage of aqueous PLP. There is a need to develop pharmaceutical forms of PLP that ensure dose accuracy and avoid potentially unsafe impurities with the aim of enhancing safety and compliance.